2016
DOI: 10.3892/mmr.2016.6057
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-375 inhibits oral squamous cell carcinoma cell migration and invasion by targeting platelet-derived growth factor-A

Abstract: Abstract. serves an important role in cancer development and growth. However, little is known about the role of miR-375 in the regulation of oral squamous cell carcinoma (OSCC) metastasis and invasion. The present study measured the expression levels of miR-375 in Tca8113, UM2, UM1 and CAL-27 cell lines, using reverse transcription-quantitative polymerase chain reaction. The results demonstrated that miR-375 expression levels were significantly reduced in UM1 and CAL-27 (highly metastatic) compared with Tca81… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 20 publications
(17 reference statements)
2
13
0
Order By: Relevance
“…Recent studies have emphasized the utility of mir-375 as a biomarker for detection of tongue cancer ( 23 ), malignant transformation of oral lesions ( 39 ), and late stages of oral cancer ( 28 ). Mir-375 has been down-regulated in metastatic oral cancer cell lines compared with less metastatic cells, and mir-375 induced cell migration and invasion by direct targeting the platelet-derived growth factor-A ( PDGF-A ) ( 40 ). Mir-375 mediates the trichostatin-A-induced radiosensitization of tongue cancer ( 41 ), indicating a therapeutic potential of mir-375.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have emphasized the utility of mir-375 as a biomarker for detection of tongue cancer ( 23 ), malignant transformation of oral lesions ( 39 ), and late stages of oral cancer ( 28 ). Mir-375 has been down-regulated in metastatic oral cancer cell lines compared with less metastatic cells, and mir-375 induced cell migration and invasion by direct targeting the platelet-derived growth factor-A ( PDGF-A ) ( 40 ). Mir-375 mediates the trichostatin-A-induced radiosensitization of tongue cancer ( 41 ), indicating a therapeutic potential of mir-375.…”
Section: Discussionmentioning
confidence: 99%
“…All 14 genes contained potential HREs in their promoter regions; of them, COL18A1, RRAS2, CORO1A, F2RL1, and PTP4A1 had not previously been suggested as being regulatory targets of HIF-1α (Supplementary Table 3). Our prior work showed that VEGFA, IL6, and PDGFB are overexpressed in OSCC 21 , while other studies found that THBS1 34 , PDGFA 35 , and SPHK1 36 are upregulated and able to promote migration and invasion activities in OSCC. These six genes were previously reported as being regulated by HIF-1α in OSCC.…”
Section: Discussionmentioning
confidence: 83%
“…Theoretically, by silencing tumor-promoting miRNAs and inducing the expression of tumor-suppressing miRNAs synchronously, it is possible to treat oral carcinoma. Specific miRNAs have multiple target genes, for example, miR-375 targets IGF1R (32), platelet-derived growth factor subunit A (131), Kruppel-like factor 5 (80) and solute carrier family 7 member 11 (81); miR-138 targets AKT serine/threonine kinase 1 (82) and yes-associated protein 1 (83); miR-203 targets B lymphoma Mo-MLV insertion region 1 homolog (84), semaphorin 6A (85) and phosphatidylinositol-4,5-bisphosphate 3-kinase catalytic subunit α (86); and miR-221 targets tissue inhibitor of metalloproteinase 3 (114) and phosphatase and tensin homolog (PTEN) (115). A possible treatment strategy may involve anticancer drugs that selectively regulate the expression of such miRNAs.…”
Section: Conceivable Therapeutic Value Of Mirnasmentioning
confidence: 99%